2017
DOI: 10.1039/c7se00373k
|View full text |Cite
|
Sign up to set email alerts
|

Vapor-fed solar hydrogen production exceeding 15% efficiency using earth abundant catalysts and anion exchange membrane

Abstract: A vapor-fed solar hydrogen generator with KOH-doped poly(vinyl alcohol) anion exchange membrane flanked with NiFe and NiMo catalysts is demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 47 publications
0
51
0
Order By: Relevance
“…However, the high operating temperature means a higher energy demand and a higher operational cost compared to rival technologies that typically operate below 100 o C. In addition, the high temperature they are still susceptible to physical damage 34,35 . To circumvent some of the aforementioned issues, recent studies have shown an interest towards using water vapour (including saline water) as water feeds in both PEMWE and AEMWE [36][37][38] . In these cases, air was bubbled through a saline aqueous media to reach high levels of humidity and gas phase electrolysis was conducted.…”
Section: Reactor Design Considerationsmentioning
confidence: 99%
“…However, the high operating temperature means a higher energy demand and a higher operational cost compared to rival technologies that typically operate below 100 o C. In addition, the high temperature they are still susceptible to physical damage 34,35 . To circumvent some of the aforementioned issues, recent studies have shown an interest towards using water vapour (including saline water) as water feeds in both PEMWE and AEMWE [36][37][38] . In these cases, air was bubbled through a saline aqueous media to reach high levels of humidity and gas phase electrolysis was conducted.…”
Section: Reactor Design Considerationsmentioning
confidence: 99%
“…The MoS x /TiO 2 can be expected to accommodate to various device structure for solar hydrogen production. Ronge and co‐workers have adopted a vapor‐fed electrolyzer equipped with an anion exchange membrane and driven by external solar electricity . Using NiFe and NiMo as the electrocatalysts for water oxidation and reduction separately, the device achieved an average STH value of 15.1%, verifying the effectiveness and feasibility of the electrolyteless device for large‐scale water splitting.…”
Section: Fundamental Requirements Of Materials For Photoelectrocatalymentioning
confidence: 99%
“…[22] This IPEC cell may be fed by liquid water or water vapor in combination with a solid polymer electrolyte, such as Nafion. [22][23][24][25][26][27] We demonstrated over 100 h of steady solar-tohydrogen (STH) efficiency under a combination of steady-state and diurnal simulated light. [22] There was no noticeable degradation of the Pt and Ir electrocatalysts or the PV when appropriate water management, to limit water contact with the PV, was employed.…”
Section: Introductionmentioning
confidence: 99%